INFECTIOUS DISEASES OF KHMER IMMIGRANTS IN THE UNITED STATES: REVIEW OF PUBLISHED REPORTS - Pilsczek, Florian H (Journal of Ayub Medical College Abbottabad, 2011)
Infectious diseases are influenced by where patients have lived or travelled in the past, e.g., infection with Schistosoma mekongi can be acquired during freshwater contact in Cambodia, but not in the United States. Here the infectious diseases of Khmer immigrants in the United States were studied by reviewing published reports. Thirteen case series and 9 case reports of 5,222 patients were identified. Most reports were of infections with gastrointestinal parasites (8, 36%), Plasmodium species (3, 14%), Mycobacterium tuberculosis (3, 14%), and Mycobacterium leprae (2, 9%). Other reports included infections with Burkholderia pseudomallei, Trichinella spiralis, and Schistosoma japonicum. In conclusion, Khmer patients in the US can be infected with different gastrointestinal parasites, different extrapulmonary forms of tuberculosis have been reported, and 2 reports of M. leprae were identified. A country-specific database for origin and current residence for Khmer and other immigrant groups providing access to specialised information may be useful for clinicians taking care of immigrants. Keywords: International Health, Immigrants, Cambodia